The Use of Regression, Log, and Top Models to Determine the Influencing Factors On Having Diabetes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Statistical models have a major role in the health field, especially when dealing with diabetes and it is called diabetes sometimes (Diabetes Mellitus) is one of the chronic diseases and universally common, and is usually produced when the body is unable to produce sufficient quantities of the hormone insulin, or when the body is unable To benefit from insulin, which leads to high levels of sugar or blood glucose, and there are factors that lead to this disease, including age, blood sugar, social status, and educational qualification. Given that high sugar is a serious disease that affects a person without feeling it and that leads to sudden death so In this research, the traditional regression model was used and compared with the regression model of Topit, Probet, and Logit, which aims to know the factors affecting diabetes, so the researcher concluded that both the traditional least squares method and the method of repentance in the morale of the variables and the moral value of the model as a whole for both methods were converging while they were compatible Logit and Probet method in the results of the variables significance, Pseudo R2 value and model significance